2021
DOI: 10.1177/1010539521998861
|View full text |Cite
|
Sign up to set email alerts
|

Increased Prevalence of Breakfast Skipping in Female College Students in COVID-19

Abstract: Going outside the house was nationally restricted among countries affected with coronavirus disease 2019 (COVID-19). This study aimed to determine the prevalence of breakfast skipping among female college students during the COVID-19 emergency period. The cross-sectional survey was conducted from May 15, 2020, to June 1, 2020, among 164 female junior college students through the online survey using Google Form. Population of breakfast skipping during the emergency (26.7%) was significantly increased compared w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 9 publications
0
14
1
Order By: Relevance
“…Intake of breakfast slightly increased over number of days from baseline to FU2, whereas number of days with lunch and dinner slightly decreased. These results conflict a previous study in which female university students reported skipping breakfast more often during the pandemic [55]. Furthermore, fewer morning snacks and afternoon snacks were reported, respectively, during the pandemic as compared to before.…”
Section: Amphetaminecontrasting
confidence: 99%
“…Intake of breakfast slightly increased over number of days from baseline to FU2, whereas number of days with lunch and dinner slightly decreased. These results conflict a previous study in which female university students reported skipping breakfast more often during the pandemic [55]. Furthermore, fewer morning snacks and afternoon snacks were reported, respectively, during the pandemic as compared to before.…”
Section: Amphetaminecontrasting
confidence: 99%
“…We found that 24 studies met the inclusion criteria and assessed the dietary changes of college students during the pandemic (30,31,32,34,35,36,37,48,49,50,51,52,53,54,55,56,57,58,59,60,61,62,63,64) . Most of these investigations were cross-sectional and measured the college students' diets via online questionnaires (supplemental table).…”
Section: Dietmentioning
confidence: 99%
“…There was an increase in the prevalence of binge eating (35,63) , breakfast skipping (31,61,65) , cooking (31,32,35,36,37,56) , and snacking (31,32,35,51,54,58,59,64,66) in various student populations during the pandemic.…”
Section: Dietary Habitsmentioning
confidence: 99%
See 1 more Smart Citation
“…With the modification in sleep schedule comes the loss of meal routines as well. Breakfast was no longer an essential early morning meal for those who were accustomed to eating within a few hours of waking up [12,13]. Breakfast is considered an essential meal of the day, and skipping it appears to trigger mental distress [14,15].…”
Section: Introductionmentioning
confidence: 99%